Bridging the gap between OSS Compliance and Contribution. Adapting for Strategic Open Source - Lundin, Sanna; Smail, Sophia (My University, 2020)
The automotive industry is currently undergoing an incredible amount of change and the challenge of developing advanced driver-assistance systems and autonomous driving systems is not one that can be done by one actor alone. In this context, it is now more relevant than ever for automotive firms to adapt to a more open, collaborative model of software development and the introduction of an open source software (OSS) strategy within the firm will be a critical step in realizing their overall strategic aims. The aim of the study was to develop a framework or model that explains how automotive firms manage the transition from operational OSS to strategic OSS usage, specifically the development of a contribution framework after establishing a compliance process. While strategic and organizational structure-related decisions are often highly dependent on firm-specific circumstances, the study intends to contribute a framework for firms to engage in strategic open source usage by developing a contribution process which aligns with the firm’s strategic objectives. Based on a multiple case study on Scania AB and Volvo Cars Corporation, three main factors related to OSS contribution were assessed: design of the contribution process, aspects relevant to software artifact evaluation, and organizational challenges faced while moving to a strategic OS paradigm. The findings of the study suggest that a cross-organizational team consisting of technical, legal and business perspectives be represented in the evaluation of contribution requests and that inner source development methods offer a way for organization to address the challenges in promoting OSS awareness within the company as part of the shift towards a more strategic engagement with OSS.
Keywords: Open source software; Inner source development; Open innovation; Organizational collaboration; Automotive; Autonomous systems